Determination the Gene Expression Levels of adhesins and Extracellular Enzymes Genes in Candida albicans biofilm producer by Quantitative Real Time PCR Technique (qRT-PCR) - Najwan Abbas Mohammed; Hamzia Ali Ajah; Nemat Jamel Abdulbaqi (Indian Journal of Forensic Medicine & Toxicology, 2021)
In the present study, all C. albicans were biofilm producers with variable strength. Molecular study ofvirulence genes correlated with biofilm C. albicans showed that HWP1, ALS1, ALS3, SAP5, PLB1 and LIP8genes were detected in 100% of C. albicans from vaginal and oral infections. In addition to that quantitativereal time PCR technique show that ITS1 was used as the housekeeping gene and was shown to be stablyexpressed throughout all biofilm conditions and HWP1, ALS1, ALS3, SAP5, PLB1 and LIP8 where 100%expressed in all ten tested C. albicans. It was appeared that adhesins genes such as HWP1, ALS1 and ALS3were highly expressed in HBF and less expressed in LBF, whereas in very low BF producers the fold upregulation were not particularly high, but they were over expressed in strong biofilm producers in both ofvaginal and oral isolates. The average of gene expression folding show that SAP5 and PLB1 were highlyexpressed among vaginal isolates rather than oral ones, in contrast, ALS1, HWP1 and LIP8 were predominantexpressed among oral isolates, whereas ALS3 was higher in vaginal isolates than oral with little differences.Gene expression levels by q RT-PCR show that SAP5 and PLB1 were up-regulated in both of HBF andLBF producers, and they were highly expressed among the ten tested isolates. The over expressions ofSAP5 and PLB1 genes were observed in vaginal isolates with high biofilm. The current study found anoverexpression of adhesins such as HWP1, ALS1, ALS3, are responsible in strength of biofilm formationin C. albicans isolated from oral and vaginal infection with different ages and different clinical states,in addition to upregulated of extracellular hydrolytic enzymes genes belong to SAP, PLB and LIP wasimportant in biofilm formation.